Crosslinkable hyperbranched polyarylene ether nitrile water-based sizing agent and preparation method thereof

By using cross-linkable hyperbranched polyaryl ether nitrile aqueous sizing agent in carbon fiber/polyaryl ether composite materials, the problems of poor interface performance and environmental pollution of the sizing agent are solved, and the preparation of composite materials with high mechanical properties and environmental protection is achieved. .

CN119321058APending Publication Date: 2025-01-17CHANGCHUN UNIV OF TECH

Patent Information

Application Number
CN202411657954.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the prior art, the interface performance of carbon fiber/polyarylether composite materials is poor, resulting in limited mechanical properties, and commercial sizing agents are mostly solvent-based, which has problems of environmental pollution and high costs.

Method used

A cross-linkable hyperbranched polyaryl ether nitrile water-based sizing agent is used. The sizing agent undergoes a self-crosslinking reaction through the allyl functional group under heating conditions to form a network structure and improve thermal stability and solvent resistance.

Benefits of technology

It significantly improves the interlaminar shear strength of carbon fiber/polyarylene ether composite materials and maintains excellent interfacial properties in high temperature or solvent environments. The sizing agent is water-based, environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119321058A_ABST
    Figure CN119321058A_ABST
Patent Text Reader

Abstract

The invention provides a crosslinkable hyperbranched polyarylene ether nitrile water-based sizing agent and a preparation method thereof, and belongs to the technical field of sizing agents. The composition comprises the following components in percentage by mass: 0.5-6% of polyarylene ether nitrile; 0.2-5% of a surfactant, 0.2-2% of an organic solvent, and the balance of water; the structure of the polyarylene ether nitrile is similar to that of a polyarylene ether resin matrix, and when the polyarylene ether nitrile is used as a main component of the sizing agent, the excellent interfacial compatibility between the polyarylene ether nitrile and the polyarylene ether resin matrix can be ensured. The sizing agent has a composite material interface phase with high temperature resistance and solvent resistance, and the interface bonding strength of the carbon fibers and the polyarylether resin can be effectively improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a cross-linkable poly(arylether nitrile) aqueous sizing agent and a preparation method and application thereof. Background Art

[0002] In recent years, continuous carbon fiber reinforced thermoplastic composites have become the representative of advanced composite materials with advantages such as high specific strength, low density and high thermal stability. Among many thermoplastic resins, polyarylether resins are widely used in various fields due to their excellent thermal stability, solvent resistance and mechanical properties. However, due to the inert surface of carbon fiber, it is difficult for polyarylether resins with high melt viscosity to fully infiltrate with carbon fiber to form a strong interaction, resulting in poor interfacial performance of carbon fiber / polyarylether composites, which limits the application range of carbon fiber / polyarylether composites.

[0003] The interface is a medium that acts as a "bridge and bond" for stress transfer between the reinforcing carbon fiber and the resin in the composite material. A good interface can transfer the external load borne by the matrix resin to the reinforcing matrix (fiber), and through efficient stress transfer to the middle fiber reinforcement matrix, improve the bearing capacity of the overall composite material. A good interface between the resin matrix and the reinforcement matrix has the effect of inhibiting crack propagation and alleviating stress concentration. A good interface between the resin matrix and the reinforcement matrix can absorb and disperse various mechanical shocks and thermal shocks, and improve the impact resistance of the composite material. The existence of a good interface layer between the resin matrix and the reinforcement matrix of the composite material has a crucial influence on the macroscopic properties of the composite material.

[0004] Sizing is an essential process in industrial production, which can effectively improve the interface properties of composite materials. The sizing agent coated on the surface of carbon fiber is like a protective film, which can effectively block the pollution of impurities such as dust in the air and improve the operability of carbon fiber.

[0005] Most commercial sizing agents are epoxy sizing agents, which have poor compatibility with polyarylether resins and are prone to thermal decomposition within the processing temperature range of polyarylether resins, which inevitably cause defects at the interface of carbon fiber / polyarylether composites, thereby reducing the mechanical properties of the composites. At present, some scientific researchers have developed sizing agents suitable for polyarylether resins in order to solve this problem. Although the interfacial bonding properties of carbon fiber / polyarylether resin composites can be improved, most of the prepared sizing agents are solvent-based, with high costs, environmental pollution, and do not conform to the concept of green chemical development. Therefore, it is particularly important to prepare a water-based sizing agent suitable for polyarylether resins. At present, researchers prepare sizing agents by chemically modifying polyarylether resins. Due to the destruction of the regular molecular chain structure, the thermal stability and solvent resistance of the sizing agent will decrease, resulting in defects and holes formed inside the carbon fiber / polyarylether composites.

[0006] Hyperbranched polymers refer to highly branched macromolecular polymers. Because their degree of branching far exceeds that of linear polymers, they have many unique physical and chemical properties, such as spherical structure, good solubility, low melt viscosity, and abundant end groups. Among them, the spherical structure helps to reduce the entanglement between polymer molecular chains and promote the slippage between molecular chains, thereby improving the melt flow properties of the polymer; in addition, the abundant end groups can provide sites for the functionalization and high performance of hyperbranched polymers, thereby optimizing the overall material properties of the polymer.

[0007] Patent No. CN114657787A discloses a high temperature resistant soluble polyaryletherketone sizing agent. It is used to prepare composite materials based on high temperature engineering resins such as polyetheretherketone, polyetherketoneketone, polyimide, polyetherimide or polyphenylene sulfide sulfone, polyethersulfone, etc., and a high temperature resistant sizing agent for sizing the surface of reinforced carbon fiber for 3D printing materials: including a preparation method of a high temperature resistant sizing agent, a process for sizing carbon fiber with a high temperature resistant sizing agent, and a preparation process for a polyaryletherketone coated carbon fiber composite material. The high temperature resistant sizing agent is composed of a soluble polyaryletherketone, an interface agent and a solvent; it can significantly improve the interface fusion between carbon fiber, glass fiber and resin matrix, and improve the mechanical properties of composite materials and 3D printing materials. However, the sizing agent is solvent-based, which is not conducive to environmental protection, and the increase in solubility will lead to a decrease in solvent resistance. Summary of the invention

[0008] The present invention aims at the problem that the CF / PEEK composite material in the prior art has insufficient sizing agent stability and solubility resistance, and provides a cross-linkable hyperbranched polyarylethernitrile water-based sizing agent, by introducing allyl groups into the sizing agent, a self-cross-linking reaction can be achieved under heating conditions to form a network structure. The sizing agent has excellent thermal stability and good heat resistance, and is applied to carbon fiber reinforced polyarylether resin composite materials to significantly improve the interlaminar shear strength of the material.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A cross-linkable polyarylether nitrile water-based sizing agent, calculated based on a total mass fraction of 100%, comprises the following components:

[0011] Polyarylethernitrile 0.5-5%;

[0012] Surfactant 0.1-5%;

[0013] Organic solvent 0.2-2%;

[0014] The rest is water;

[0015] The polyarylethernitrile has the following structural formula:

[0016] The present invention adopts hyperbranched polyarylethernitrile with a structure similar to that of polyetheretherketone resin as the main component of the sizing agent. The hyperbranched structure has low chain entanglement and high branching, which is conducive to the mutual entanglement and diffusion of molecular chain segments with the polyetheretherketone resin matrix during the hot pressing process, and can ensure good compatibility between the carbon fiber and the resin matrix after sizing. The allyl functional group in the polymer molecular chain segment can make up for the problem of decreased thermal stability and solvent resistance of the polymer after thermal crosslinking reaction during the composite material molding process. The carbon fiber reinforced polyetheretherketone resin composite material modified by the sizing agent can still maintain excellent interface performance in high temperature or solvent phase.

[0017] The particle size of the polyarylethernitrile water-based sizing agent is 30-200 nm. The sizing agent has good dynamic stability and a small particle size range. In particular, after storage for 6 months, the particle size remains substantially unchanged and no precipitation is generated. The sizing agent can form a uniform film on the surface of the carbon fiber, and the sized carbon fiber has good wettability.

[0018] The surfactant includes one or more combinations of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, sodium lauryl aminopropionate, stearyl dimethyl betaine, lauryl dihydroxyethyl betaine, lauryltrimethylammonium chloride, OP series, EL series or Tween series compounds.

[0019] The organic solvent includes one or more combinations of dichloromethane, chloroform, methyl chloroform, 1,1-dichloroethane, or 1,2-dichloroethane.

[0020] The present invention also provides a method for preparing the cross-linkable hyperbranched polyarylethernitrile water-based sizing agent, comprising the steps of: dissolving the polyarylethernitrile in an organic solvent and stirring evenly, then dissolving a surfactant in water, pouring the organic solvent containing the polyarylethernitrile into deionized water, and performing ultrasonic shearing treatment to obtain a mixed solution; and removing the solvent to obtain the hyperbranched polyarylethernitrile water-based sizing agent.

[0021] The ultrasonic shearing treatment time is 2-30min, the power is 50-3000W, and the temperature is 10-50°C.

[0022] The cross-linkable hyperbranched poly(arylene ether nitrile) aqueous sizing agent is used for sizing treatment.

[0023] Preferably, the sizing treatment time is 10-40 seconds and the speed is 5-15 m / min. The aromatic ether resin composite material is hot-pressed to obtain a composite material with a fiber laying direction of 0°.

[0024] The polyarylether-based resin is preferably any one of polyetheretherketone, polyetherethernitrile, polyetherethersulfone, polyetherketone, polyethernitrile, polyethersulfone, polyetheretherketoneketone, polyethersulfoneketone, polyetherketoneketone, or polyetherketoneetherketoneketone.

[0025] The main component of the sizing agent, the hyperbranched polyarylether nitrile, is similar in structure to the polyarylether resin matrix, and the two have excellent interfacial compatibility. The bulky side groups in the polymer structure can make it soluble in organic solvents, and the allyl functional groups can form a cross-linked network structure during the hot pressing process, thereby forming an interfacial phase with high temperature resistance and solvent resistance.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a cross-linkable hyperbranched polyarylether nitrile sizing agent and a preparation method thereof. The sizing agent uses hyperbranched polyarylether nitrile resin as the main sizing material, and effectively solves the compatibility problem between the sizing agent and the polyarylether matrix resin according to the principle of "like dissolves like", and the sizing agent has good thermal stability; the polymer contains a large allyl side group, which can destroy the regularity of the structure and restore the solubility, so that it can be dissolved in most organic solvents. The water-based sizing agent is prepared by an emulsion solvent evaporation method; the molecular chains can be entangled and diffused with each other, which improves the interaction force between molecules; at the same time, in the hot pressing process of preparing the composite material, a cross-linked network structure is formed, thereby restoring the solvent resistance.

[0028] The method used in the invention is simple, rapid, easy to operate, easy to implement repeatedly and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is the H NMR spectrum of the poly(arylene ether nitrile) in Example 1. Figure 2 This is the thermal gravimetric curve of the poly(arylene ether nitrile) in Example 1. Figure 3 The interlaminar shear strength test results of the composite materials in Examples 1-4. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0030] The polyarylether nitrile resin is synthesized by the following method: in a nitrogen atmosphere, a bisphenol monomer, a fluorine monomer, calcium oxide and an NMP solvent are mixed and stirred, and reacted at 150-210° C. until the polymer is viscous. The mixture is then poured into a mixed solvent of deionized water and dilute hydrochloric acid to obtain a polymer solid, which is repeatedly boiled and washed with deionized water and methanol for several times, and then dried in a vacuum oven to obtain a cross-linkable hyperbranched polyarylether nitrile polymer.

[0031] Example 1

[0032] The specific structural formula of the polyarylethernitrile is as follows:

[0033]

[0034] The preparation process of the polyarylether is as follows: Under nitrogen atmosphere, trifluoromonomer (8.41 g), biseugenol (8.32 g), calcium oxide (7.11 g) and NMP (71.52 g) were mixed and stirred, and reacted at 170°C until the polymer became viscous. The mixture was then poured into a mixed solvent of deionized water and dilute hydrochloric acid to obtain a polymer solid, which was repeatedly washed with a mixed solvent of deionized water and dilute hydrochloric acid for several times, and then dried in a vacuum oven to obtain a cross-linkable polyarylethernitrile polymer.

[0035] The cross-linkable polyarylether nitrile water-based sizing agent comprises, by weight percentage of 100%, 2% polyarylether nitrile, 2% hexadecyltrimethylammonium bromide, 1% chloroform, and the remainder is deionized water.

[0036] Preparation of poly(arylene ether nitrile) water-based sizing agent:

[0037] (1) dissolving 20 g of the obtained hyperbranched poly(arylene ether nitrile) in dichloromethane to obtain a uniform solution;

[0038] (2) Add 20 g of hexadecyltrimethylammonium bromide to 960 mL of deionized water, stir thoroughly, then add the solution of step (1) and mix evenly, then perform ultrasonic shearing for 8 min to obtain a mixed solution at a power of 400 W, and keep the solution temperature at 35°C;

[0039] (3) The organic solvent is recovered by rotary evaporation to obtain a cross-linkable hyperbranched poly(arylene ether nitrile) aqueous sizing agent.

[0040] The commercial desized carbon fiber is immersed in the sizing agent prepared in step (3) for 24 seconds to obtain sizing-treated carbon fiber, and then the dried sizing-treated carbon fiber is compounded with a polyetheretherketoneketone film to prepare a prepreg. The prepreg is then cut into an appropriate size and placed in a mold coated with a release agent. The fiber is laid in a 0° direction for hot pressing to obtain a carbon fiber reinforced polyetheretherketoneketone (CF / PEEKK) composite material.

[0041] Example 2

[0042] The specific structural formula of the polyarylethernitrile is as follows

[0043]

[0044] The structure and preparation process of poly(arylether nitrile) are as in Example 1.

[0045] The cross-linkable polyarylether nitrile water-based sizing agent comprises, by weight percentage of 100%, 2% polyarylether nitrile, 2% sodium dodecylbenzene sulfonate, 1% chloroform, and the remainder being deionized water.

[0046] Preparation of poly(arylene ether nitrile) water-based sizing agent:

[0047] (1) dissolving 20 g of the obtained hyperbranched poly(arylene ether nitrile) in chloroform to obtain a uniform solution;

[0048] (2) Add 20 g of sodium dodecylbenzene sulfonate to 960 mL of deionized water, stir thoroughly, then add the solution of step (1) and mix well, then perform ultrasonic shearing for 8 min to obtain a mixed solution at a power of 400 W, and keep the solution temperature at 35° C.;

[0049] (3) The organic solvent is recovered by rotary evaporation to obtain a cross-linkable hyperbranched poly(arylene ether nitrile) aqueous sizing agent.

[0050] The commercial desized carbon fiber is impregnated in the sizing agent prepared in step (3) and the wire is fed for 24 seconds at a speed of 10 m / min to obtain sizing-treated carbon fiber. The dried sizing-treated carbon fiber is then composited with a polyetheretherketoneketone film to obtain a prepreg. The prepreg is then cut into an appropriate size and placed in a mold coated with a release agent. The fiber is laid in a 0° direction and hot-pressed to obtain a carbon fiber reinforced polyetheretherketoneketone (CF / PEEKK) composite material.

[0051] Example 3

[0052] The specific structural formula of the polyarylethernitrile is as follows

[0053]

[0054] The structure and preparation process of poly(arylether nitrile) are as in Example 1.

[0055] The cross-linkable polyarylethernitrile water-based sizing agent comprises, by weight percentage of 100%, 2% polyarylethernitrile, 2% sodium dodecyl sulfate, 1% chloroform, and the rest being deionized water.

[0056] Preparation of poly(arylene ether nitrile) water-based sizing agent:

[0057] (1) dissolving 20 g of the obtained hyperbranched poly(arylene ether nitrile) in chloroform to obtain a uniform solution;

[0058] (2) Add 20 g of sodium dodecyl sulfate to 960 mL of deionized water, stir thoroughly, then add the solution of step (1) and mix well, then perform ultrasonic shearing for 8 min to obtain a mixed solution at a power of 400 W, and keep the solution temperature at 35°C;

[0059] (3) The organic solvent is recovered by rotary evaporation to obtain a cross-linkable hyperbranched poly(arylene ether nitrile) aqueous sizing agent.

[0060] The commercial desizing carbon fiber is impregnated in the sizing agent prepared in step (3) and the wire is fed for 24 seconds at a speed of 10 m / min to obtain the sizing-treated carbon fiber, and then the dried sizing-treated carbon fiber is composited with a polyetheretherketone film to obtain a prepreg, and then the prepreg is cut into an appropriate size and placed in a mold coated with a release agent, and the fiber is laid in a 0° direction for hot pressing to obtain a carbon fiber reinforced polyetheretherketone (CF / PEEKK) composite material;

[0061] Example 4

[0062] The specific structural formula of the polyarylethernitrile is as follows

[0063]

[0064] The structure and preparation process of poly(arylether nitrile) are as in Example 1.

[0065] The cross-linkable polyarylethernitrile water-based sizing agent comprises, by weight percentage of 100%, 2% polyarylethernitrile, 2% sodium dodecyl sulfate, 1% chloroform, and the rest being deionized water.

[0066] Preparation of poly(arylene ether nitrile) water-based sizing agent:

[0067] (1) dissolving 20 g of the obtained hyperbranched poly(arylene ether nitrile) in chloroform to obtain a uniform solution;

[0068] (2) Add 20 g of sodium dodecyl sulfate to 960 mL of deionized water, stir thoroughly, then add the solution of step (1) and mix well, then perform ultrasonic shearing for 8 min to obtain a mixed solution at a power of 400 W, and keep the solution temperature at 35°C;

[0069] (3) The organic solvent is recovered by rotary evaporation to obtain a cross-linkable hyperbranched poly(arylene ether nitrile) aqueous sizing agent.

[0070] The commercial desizing carbon fiber is impregnated in the sizing agent prepared in step (3) and the wire is fed for 24 seconds at a speed of 10 m / min to obtain the sizing treated carbon fiber. The dried sizing treated carbon fiber is then composited with a polyetheretherketone film to obtain a prepreg. The prepreg is then cut into an appropriate size and placed in a mold coated with a release agent. The fiber is laid in a 0° direction and hot-pressed to obtain a carbon fiber reinforced polyetheretherketone (CF / PEEKK) composite material.

[0071] The commercial desizing carbon fiber is impregnated in the sizing agent prepared in step (3) and the wire is fed for 24 seconds at a speed of 10 m / min to obtain the sizing treated carbon fiber. The dried sizing treated carbon fiber is then composited with a polyetheretherketone film to obtain a prepreg. The prepreg is then cut into an appropriate size and placed in a mold coated with a release agent. The fiber is laid in a 0° direction and hot-pressed to obtain a carbon fiber reinforced polyetheretherketone (CF / PEEKK) composite material.

[0072] The poly(arylene ether nitrile) obtained in Example 1 was subjected to a thermal stability test, and the thermal weight loss curve is shown in FIG. Figure 2 As shown, it can be seen that the temperature at which the mass loss of the cross-linkable polyarylethernitrile is 5% is 438°C, which proves that the aqueous sizing agent prepared by the present invention has excellent heat resistance after the thermal cross-linking reaction, solves the problem of poor stability of the sizing agent in the prior art, and there is no need to worry about thermal decomposition during the composite material molding process.

[0073] The interlaminar shear strength of the sizing carbon fiber reinforced polyetheretherketone composite material was tested. The interlaminar shear strength of the composite material sizing with the sizing agent of Examples 1-4 was 72.1 MPa, 69.7 MPa, 68.2 MPa, and 70.1 MPa, respectively. Figure 3 shown.

[0074] Solubility resistance test

[0075] The fibers sized with the sizing agents of Examples 1-4 were immersed in different organic solvents at room temperature for one week and then the interlaminar shear strength data of the materials were tested.

[0076] It should be understood that the application of the present invention is not limited to the above examples, and any non-substantial changes to the present invention using this concept shall fall within the scope of protection of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments in any form according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A cross-linkable poly(arylene ether nitrile) aqueous sizing agent, characterized in that: Based on the total mass fraction of 100%, the raw material components include the following: Polyarylethernitrile 0.5-6%; Surfactant 0.2-5%; Organic solvent 0.2-2%; The rest is water; The particle size of the poly(arylene ether nitrile) aqueous sizing agent is 30-200 nm; The poly(arylene ether nitrile) has any one of the following structural formulas 。 2. The cross-linkable poly(arylene ether nitrile) aqueous sizing agent according to claim 1, characterized in that: The surfactant includes hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, sodium lauryl aminopropionate, stearyl dimethyl betaine, lauryl dihydroxyethyl betaine, lauryl trimethyl ammonium chloride, or one or more combinations of Tween series compounds.

3. The cross-linkable poly(arylene ether nitrile) aqueous sizing agent according to claim 1, characterized in that: The organic solvent includes one or more combinations of dichloromethane, chloroform, methyl chloroform, 1,1-dichloroethane, or 1,2-dichloroethane.

4. The method for preparing a cross-linkable poly(arylene ether nitrile) aqueous sizing agent according to any one of claims 1 to 3, characterized in that: Includes steps: The polyarylethernitrile is dissolved in an organic solvent and stirred evenly. Then a surfactant is dissolved in water, the organic solvent containing the polyarylethernitrile is poured into deionized water, and ultrasonic shearing is performed to obtain a mixed solution; and the solvent is removed to obtain the cross-linkable polyarylethernitrile water-based sizing agent.

5. The method for preparing the cross-linkable poly(arylene ether nitrile) aqueous sizing agent is characterized in that: The ultrasonic shearing treatment time is 2-30 min, the power is 50-4000 W, and the temperature is 10-50°C.

6. Use of a hyperbranched poly(arylether nitrile) aqueous sizing agent according to any one of claims 1 to 5 in the field of preparing carbon fiber reinforced poly(arylether ketone) composite materials, characterized in that: The steps are as follows: The desizing commercial carbon fiber is immersed in the sizing agent described in claim 5 for 10-40 seconds to obtain the sizing-treated carbon fiber, which is then dried at a temperature of 90-110°C, and then the sizing-treated carbon fiber is composited with a polyaryletherketone film to prepare a prepreg, and then the prepreg is cut into an appropriate size and placed in a mold coated with a release agent, and the fiber is laid in a 0° direction for hot pressing to obtain a carbon fiber reinforced polyarylether composite material.

Citation Information

Patent Citations

  • Carbon fiber modified with crystalized crosslinkable polyaryletherketone sizing agent and preparation method of carbon fiber

    CN110820315A

  • Phenolphthalein modified polyaryletherketone water-based sizing agent as well as preparation method and application thereof

    CN113563577A

  • Crosslinkable polyarylene ether nitrile water-based sizing agent as well as preparation method and application thereof

    CN114687213A

  • Hyperbranched polycarbonate and its production process

    JP2007161928A

Cited By

  • Cross-linked polymer modified carbon fiber, preparation method and composite material

    CN121363113A